Trend of Sudden Unexpected Death in Epilepsy Incidence Rate in Rural West China - Wang, Haijiao; Chen, Deng; He, Jun; He, Yujin; Liu, Ling; Zhou, Dong (Frontiers in Neurology, 2021)
Objectives: To explore the trend of sudden unexpected death in epilepsy (SUDEP) incidence rate over time in rural west China. Methods: We scanned probable SUDEP patients from the epilepsy program between 2010 and 2019 in rural West China and performed a verbal autopsy for each eligible patients. We calculated the crude and sex adjusted incidence rate of SUDEP per person year over calendar year and the year of follow up. We calculated the incidence rate ratio (IRR) with Poisson model in STATA 12.0 and calculated the annual percentage change (APC) and average annual percentage change (AAPC) in Joinpoint Trend Analysis Software 4.8.0.1, to analysis the trend of SUDEP incidence rate. Results: In 2010-2019, 44 probable SUDEP was identified from 10128 patients with total person-year of 31347. The crude and sex adjusted incidence rate of SUDEP was 1.40‰ and 1.45‰. 56.8% (25/44) probable SUDEP had no GTCS 3 months before their death. The incidence of probable SUDEP decreased significantly in calendar year (APC= -11.7, 95% CI : -21.7 to -0.3) and in time of follow up (AAPC = -21.2, 95% CI : -34.3 to -5.4). Comparing the first five years in follow up with the subsequent three years, the incidence rate of SUDEP decreased significantly (estimated IRR = 0.4, 95% CI: 0.2 to 0.8). Significance: SUDEP happened to 1.4 cases per thousand patient years in convulsive epilepsy in rural west China between 2010 and 2019. The incidence rate of SUDEP presented a downward trend over the time of follow up.